Utilizing End-Tidal Carbon Dioxide to Diagnose Diabetic Ketoacidosis in Prehospital Patients with Hyperglycemia. Issue 3 (15th June 2020) - Hunter, Christopher; Putman, Monty; Foster, Jermaine; Souers, Amy; Rodriguez, Alexa; Zuver, Christian; Papa, Linda
Abstract: Background: Early identification of diabetic ketoacidosis (DKA) may improve clinical outcomes. Prior studies suggest exhaled end tidal carbon dioxide (ETCO2) provides a non-invasive, real-time method to screen for DKA in the emergency department (ED). Methods: This a retrospective cohort study among patients who activated Emergency Medical Services (EMS) during a one-year period. Initial out-of-hospital vital signs documented by EMS personnel, including ETCO2 and first recorded blood glucose level (BGL), as well as in-hospital records, including laboratory values and diagnosis, were collected. The main outcome was the association between ETCO2 and the diagnosis of DKA. Results: Of the 118 patients transported with hyperglycemia (defined by BGL >200), six (5%) were diagnosed with DKA. The mean level of ETCO2 in those without DKA was 35mmHg (95% CI, 33-38mmHg) compared to mean levels of 15mmHg (95% CI, 8-21mmHg) in those with DKA (P <.001). The Area Under the Receiver Operating Characteristics (ROC) Curve (AUC) for ETCO2 identifying DKA was 0.96 (95% CI, 0.92-1.00). The correlation coefficient between ETCO2 and serum bicarbonate (HCO3) was 0.436 (P <.001) and the correlation coefficient between ETCO2 and anion gap was -0.397 (P <.001). Conclusion: Among patients with hyperglycemia, prehospital levels of ETCO2 were significantly lower in patients with DKA compared to those without and were predictive of the diagnosis of DKA. Furthermore, out-of-hospital ETCO2 was significantly correlated with measures of metabolic acidosis.